Eyewear in Forensic Investigations: Unveiling Evidence - Ruchika Sah (International Journal of Medical Toxicology and Legal Medicine, 2024)
Forensic investigations are essential to the criminal justice system's efforts to solve crimes and maintain the rule of law. Primarily, they depend on precise and reliable proof. One aspect of this intricate profession that is often overlooked is the significance of eyewear in the collection and interpretation of data. Glasses and customized lenses serve a variety of purposes in maintaining the objectivity of investigations and enhancing the visual analysis of crime scenes, all of which are advantageous to both parties. Eyewear is ubiquitous in today's world. Whether they are present or absent at a crime scene, glasses, contact lenses, and goggles can provide crucial information about the events that took place there. Eyeglass evidence is significant not just for its physical presence but also for its presence in the realm of traces. Particles that adhere to glasses or frames include hair, fibers, and human fluids; these particles can be crucial pieces of forensic evidence. Eyewear is utilized in forensic investigations for a variety of purposes, including both eye protection and visual enhancement. Protective eyewear, which guards against airborne contaminants, chemical spills, and bloodborne diseases, is the first line of defense for forensic investigators. Various protective eyewear styles, materials, and ergonomic designs will be explored to highlight their crucial role in ensuring the safety of investigators while preserving the integrity of the evidence. From the analysis of lens artifacts to the distinctive imprints left by eyeglasses, this study aims to give a comprehensive understanding of how eyewear can function as an essential and sometimes overlooked source of forensic evidence.